A Response to Alon Goshen-Gottstein’s "The New Covenant - Jeremiah 31:30-33 (31:31-34) in Jewish Interpretation" - Cunningham, Philip A. (Studies in Christian-Jewish Relations, 2020)
No abstract is available.